UJI AKTIVITAS ANTIFUNGI EKSTRAK ANGGUR LAUT (Caulerpa sp.) ASAL PULAU GESER KABUPATEN SERAM BAGIAN TIMUR TERHADAP FUNGI Candida albicans - Aulia Debby Pelu; Maryam Lihi; Moh. Nurul Iman Wokas (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Sea Grape (Caulerpa sp.) is a group of seaweed which is a macroalgae belonging to the Caulerpaceae family . Sea Grape very potential as a new antifungal drug because it contains secondary metabolites of saponins and flavonoids that can inhibit the growth of the fungus Candida albicans . The purpose of this study was to determine the content of secondary metabolites present in sea grapes and antifungal activity test of sea grapes (Caulerpa sp.) which was extracted using 70% ethanol as a solvent against the fungus Candida albicans. The antifungal activity was tested using the disc diffusion method with several concentrations of 5%, 10%, 25%, 50%, 85, 130%, 185%, and 250%, ketoconazole as a positive control and aquadest as a negative control. The results showed that the extraction of sea grapes contains secondary metabolites, namely: Saponins, Flavonoids, Tannins and Steroids capable of inhibiting the growth of the fungus Candida albicans, at a concentration of 25% with an inhibition zone diameter of 12.5 mm, 50% diameter of the inhibition zone 14.5 mm, 130% the diameter of the inhibition zone is 17.5 mm, 185% the diameter of the inhibition zone is 19 mm and 250% with the diameter of the inhibition zone is 22mm. The test results showed that the effective and very strong concentration of inhibiting the growth of Candida albicans was at a concentration of 250% with an inhibition zone of 22 mm.